CFD simulation methodology for gas-solid flow in bypass pneumatic conveying – A review. (October 2017) - Wang, Ying; Williams, Kenneth; Jones, Mark; Chen, Bin
Highlights: Different numerical model are described and compared for pneumatic conveying. Fluidisation charts of different materials with flow modes boundaries are showed. Guidance on what frictional approach to use for CFD analysis is provided. A flow chart for the CFD methodology of bypass pneumatic conveying is demonstrated. Abstract: This paper presents a review of numerical models for simulation of gas-solid flow in bypass pneumatic conveying. The kinetic theory, conventional frictional-kinetic model and a new modified frictional-kinetic model are described in some detail. The experimental results for pressure drops based on a number of test cases are presented and compared with numerical results obtained with different numerical models. The convergences of the modified frictional-kinetic model with different values of constants are also illustrated. Moreover, the fluidisation charts of different materials with flow mode boundaries are presented to provide guidance on what frictional approach to use for Computational Fluid Dynamics (CFD) analysis of gas-solid flow in a bypass pneumatic conveying system. Furthermore, a flow chart for the CFD simulation methodology of bypass pneumatic conveying is demonstrated. These outcomes and the associated design guidelines could assist in choosing the most appropriate models for simulation of pneumatic conveying.